Stem cell – based gene therapy - Nazir, Z.; Irshad, S. (Вiopolymers and Cell, 2013)
Stem cells have huge potential for regenerative medicine. Adult stem cell (HSC)-based therapies have been proved to be safe and efficient for several decades, and adult MSC therapies are showing efficacy in some experiments while in other trials mixed results are obtained such as only short lived effects due to poor cellular retention or other reasons that have to be further tested. Although iPSCs might suggest a great hope for the stem cell therapy, still there are important safety issues to be considered before these cells are marketed for clinical trials. However, the advanced potential to generate stem cell lines, matched to a particular patient, and to perform homologous gene correction or targeted transgene insertion into a safe dock site in the genome prior to further expansion and differentiation offer great prospects for future regenerative medicine. Furthermore, the development of the recombinant adeno-associated virus (rAAV) technology and the use of the Zinc Finger Nuclease (ZFN) technology are promoting the homologous recombination as a best possible tool for stem cell-based gene therapy.